International, evidence-based consensus diagnostic criteria for HHV-8–negative/idiopathic multicentric Castleman disease - Fajgenbaum, David C. (Blood, 2017)
Human herpesvirus-8 (HHV-8)–negative, idiopathic multicentric Castleman disease (iMCD) is a rare and life-threatening disorder involving systemic inflammatory symptoms, polyclonal lymphoproliferation, cytopenias, and multiple organ system dysfunction caused by a cytokine storm often including interleukin-6. iMCD accounts for one third to one half of all cases of MCD and can occur in individuals of any age. Accurate diagnosis is challenging, because no standard diagnostic criteria or diagnostic biomarkers currently exist, and there is significant overlap with malignant, autoimmune, and infectious disorders. An international working group comprising 34 pediatric and adult pathology and clinical experts in iMCD and related disorders from 8 countries, including 2 physicians that are also iMCD patients, was convened to establish iMCD diagnostic criteria. The working group reviewed data from 244 cases, met twice, and refined criteria over 15 months (June 2015 to September 2016). The proposed consensus criteria require both Major Criteria (characteristic lymph node histopathology and multicentric lymphadenopathy), at least 2 of 11 Minor Criteria with at least 1 laboratory abnormality, and exclusion of infectious, malignant, and autoimmune disorders that can mimic iMCD. Characteristic histopathologic features may include a constellation of regressed or hyperplastic germinal centers, follicular dendritic cell prominence, hypervascularization, and polytypic plasmacytosis. Laboratory and clinical Minor Criteria include elevated C-reactive protein or erythrocyte sedimentation rate, anemia, thrombocytopenia or thrombocytosis, hypoalbuminemia, renal dysfunction or proteinuria, polyclonal hypergammaglobulinemia, constitutional symptoms, hepatosplenomegaly, effusions or edema, eruptive cherry hemangiomatosis or violaceous papules, and lymphocytic interstitial pneumonitis. iMCD consensus diagnostic criteria will facilitate consistent diagnosis, appropriate treatment, and collaborative research.